An Empirical Investigation between FDI, Tourism, and Trade on CO2 Emission in Asia: Testing Environmental Kuznet Curve and Pollution Haven Hypothesis - Dwi Haryanto, Rossanto; Rahmawati, Yessi; Altamirano, Omar Guillermo Rojas; Ahsani, Salsabila Fahar; Hudang, Adrianus Kabubu; Haryanto, Tri (International Journal of Energy Economics and Policy, 2022)
This study aims to analyze the influence of foreign direct investment, tourism, exports, and imports on carbon dioxide (CO2) emissions in the High-Income State, Upper-Middle Income, and Lower-Middle-Middle Income in Asia during the period of 2010 to 2019. This study uses the Poisson Pseudo-Maximum Likelihood (PPML) method. The results of this study indicate that Environmental Kuznets Curve Hypothesis (EKC) is valid in the country of High Income and Upper-Middle Income. In addition, there is a non-linear relationship between foreign direct investment (FDI), tourism, Export, and imports on carbon dioxide (CO2) emissions. The interaction variables, which are a foreign direct investment with tourism and foreign direct investment with Export. Each of them is reducing carbon dioxide emissions only in high-income countries. Meanwhile, the interaction variables between foreign direct investment and imports reduce carbon dioxide emissions in high-income countries. However, it increases the carbon dioxide emissions in the upper-middle-income country